KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS DESKRIPSI DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 1 BATANG KAPAS - Ramadhan, Zicrie; R.,, Syahrul (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This article reveals the contribution of skills reading comprehension text descriptions to writing skills text description grade students VII SMP Negeri Batang Kapas 1. The purpose of this research there are three. First, it describes the skills of reading comprehension text description grade VII SMP Negeri 1 field. Second, it describes the writing skills text description grade VII SMP Negeri 1 field. Third, describing the contribution of the intermediate reading comprehension text descriptions against writing skills text description grade VII SMP Negeri 12 field. The design used in this research is the design contribution. This research population is grade VII SMP Negeri Padang are registered on the 12th school year 2018/2019, i.e. as many as 286 students. The sample in this research are determined by proportional random sampling of 20% of the population, i.e. 54 students. Research data is a score test. The data obtained through two types of tests i.e. objective tests to measure the skills of reading comprehension text description and performance tests to measure the skills of writing a text description.. First, the skills of reading comprehension text description grade VII SMP Negeri Padang 12 are on good qualifications (B) by the value of the average 80.09. Second, the skills of writing text descriptions grade VII SMP Negeri Padang 12 are on good qualifications (B) with an average of 80.86. Third, there is a contribution reading skills in the description text to the skills of writing description texts of class grade VII SMP Negeri Padang 1 at 62.73% Kata kunci: Korelasi, Keterampilan, Membaca Pemahaman, Menulis, Teks Deskripsi